Physico-chemical characterization of bacterial and hemagglutinins from the serum of the mud crab Scylla serrata - S S Jayaraj; R Thiagarajan; M Arumugam; S Vincent (Invertebrate Survival Journal, 2010)
A naturally occurring hemagglutinin (HA), with activity against bacteria and yeast cells were detected in the serum of Scylla serrata using mammalian erythrocytes (RBC), various bacteria and yeast as indicator cells. The serum gave highest HA titer with rabbit RBC, tripsinized yeast and Vibrio fluvialis. An analysis of the physico-chemical properties of the HA showed it to be specifically dependent on the presence of Ca2+ for its activity, stable between pH 7 to 9 and showed thermal stability between 10 to 30 °C. Further studies demonstrated that the HA is precipitable by ammonium sulphate and TCA. HA- inhibition assays performed with carbohydrates revealed that the serum HA was specific for non-reducing terminal glucose with 1-2 glucosidic linkages. Thus this agglutinin appears to be unique among all the known crustacean agglutinins.